REVOLUTIONIZING ENGLISH GRAMMAR INSTRUCTION THROUGH INTERACTIVE METHODOLOGIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The teaching of English grammar has long been perceived by many learners as a dry, arduous, and often frustrating endeavor. Traditionally, grammar instruction has relied heavily on rote memorization of rules, endless drills, and decontextualized exercises, often leading to a superficial understanding rather than genuine communicative competence. This conventional approach, while aiming for accuracy, frequently stifled student creativity, diminished motivation, and failed to bridge the gap between knowing a rule and applying it effectively in real-world communication. However, the evolving landscape of language education, driven by advancements in linguistic theory and pedagogical research, increasingly champions a paradigm shift: a move towards dynamic, interactive methodologies that fundamentally transform how grammar is taught and acquired. This article explores the theoretical underpinnings, practical applications, numerous benefits, and inherent challenges of interactive grammar teaching, emphasizing its indispensable role in fostering deeper understanding, enhanced retention, and authentic communicative proficiency among English language learners (ELLs). The aim is to provide a comprehensive guide for educators seeking to revolutionize their grammar classrooms into engaging, student-centered learning environments where grammar is not merely learned, but actively experienced and utilized.